Post-transplant lymphoproliferative disorder risk and outcomes in renal transplant patients treated with belatacept immunosuppression - Koff, Jean L.; Karadkhele, Geeta M.; Switchenko, Jeffrey M.; Rupji, Manali; Little, Kendra; Larsen, Christian P. (Frontiers in Transplantation, 2024)
Introduction. Post-transplant lymphoproliferative disorder (PTLD) is a rare but life-threatening malignancy that arises in the setting of immunosuppression (IS) following solid organ transplant. IS regimens containing belatacept have been associated with increased risk of PTLD in Epstein-Barr virus (EBV)-seronegative renal transplant recipients, and belatacept use is contraindicated in this population. However, the impact of belatacept-based regimens on PTLD risk and outcomes in EBVseropositive renal transplant recipients is less well characterized.A case-control study was conducted to investigate how combinatorial IS regimens impact risk of PTLD and survival outcomes in renal transplant recipients at a large transplant center, 2010-2019. Seventeen PTLD cases were identified and matched 1:2 to controls without PTLD by age, sex, and transplanted organ(s). We compared baseline clinical characteristics, examined changes in IS regimen, viral loads, and renal function over time, and evaluated time-to-event analyses including graft rejection and survival.Results. PTLD cases largely resembled matched controls in terms of baseline characteristics, although expected differences in EBV serostatus trended towards significance (42.9% PTLD cases were donor-positive/recipient negative vs. 8.3% controls, p=.063). PTLD cases were not more likely to have received belatacept than controls. Belatacept was not associated with graft rejection or failure, re-transplant, hospitalization, or decreased survival.Conclusions. Belatacept was not associated with an increased risk of PTLD, and was not associated with decreased survival in either PTLD cases or in the entire cohort. Our case-control study supports the concept that belatacept remains a safe and effective option for IS in EBV-seropositive renal transplant patients.